“Making a difference”: Interpreting responsivity ambience for parole work - Micheal P. Taylor; Rosemary Ricciardelli; Randy Shively (Heliyon)
In this article, we draw on qualitative interview data (n = 150) from parole officers (POs) employed in Canada's federal correctional service. Our analysis interprets job satisfaction, accountability, and relational aspects of POs' work, taking a semi-grounded constructivist approach. We discovered correctional workers, such as probation and parole officers, engage in transformational relationships within their workplace environments. However, given economic, social, and political constraints, we question how these change agents actually ‘make a difference’ in practice. Fidelity to core correctional practices suggests therapeutic alliances are fundamental to intervention. Emergent in our discoveries is how the workplace environment, organizational climate and culture, and penal atmosphere mediate reflexive experiences that inspire motivation, morale, and change. However, our interpretation and situational awareness of parole adds to a lacuna in knowledge about therapeutic relationships in correctional work generally and the responsivity principle specifically for sensemaking about how interventions may sometimes become iatrogenic. We found that POs negotiate their relationships with those under supervision as much as with fellow correctional workers. Responsivity ambience pertains to consolidation and conceptual clarity concerning how corrections, in its public safety mandate, induces in/efficacy. Through discussion, we theorize how securitized settings affect well-being and provide practical insights to converge on the rehabilitative ideal and criminal desistance.